Unilateral isolated dislocation at the lumbosacral junction: lateral flexion-distraction as a major vector in the mechanism of injury: case report and trauma mechanism analysis - Krbec, Martin; Hraběta, Pavel (European spine journal, 2011)
The description of the unusual mechanism of the trauma to lumbosacral junction is given based on the analysis of the clinical case. The injury of a patient with unilateral dislocation at the L5-S1 intervertebral joint without a bone lesion in this segment is reported. The patient suffered the injury by falling on one side from a height of 8 m. The trauma mechanism is documented by MRI findings and a 3D CT reconstruction of the paravertebral muscles and soft tissues on the injured side, whilst showing intact structures on the contralateral side. This, together with the cause of injury (a fall on the side), provides evidence for forced lateral flexion-distraction being the major vector of the trauma event. Such mechanism of this injury was not taken in account by other authors yet. This type of injury is difficult to classify using the Magerl classification system. The very rare injury has been mentioned in the literature only occasionally.
Keywords: dislokace kloubu; křížová kost; Magnetic Resonance Imaging; bederní obratle; Adult; dospělí; magnetická rezonanční tomografie; Humans; mužské pohlaví; Male; lidé; Radiography; Sacrum; Lumbar Vertebrae; Joint Dislocations; radiografie